RESEARCH ON THE RELATIONSHIP BETWEEN LOAD ANALYSIS METHOD AND FATIGUE OF LOWER CONTROL ARM - DU Jian; YU RenJie; XIAO Pan; DONG GuoJiang (Jixie qiangdu)
To explore the influence of virtual road surface method,virtual iteration method and fixed body method on the damage of lower control arm,the data from the test site was used. The accuracy of vehicle multi-body dynamics model was verified by suspension K＆C test and vehicle controllability and stability test. The six-component force signal of wheel center simulation value was compared with test value in the time domain and the frequency domain. The analysis results show the accuracy of 3 D virtual road and tire model; Comparison of simulation value of three methods and test value of the vertical acceleration of the wheel center shows virtual iteration method has the highest precision,and fixed body method has the worst precision. From the perspective of fatigue simulation,the results show that virtual iteration method and virtual road surface method have the same damage distribution to lower control arm. Fixed body method is quite different from the two,and is more conservative. The simulation results of lower control arm under the three load methods meet the durability of the test field.,which was consistent with the test results of indoor bench.